Simple Oxazolidine Chiral Diene Ligands for Enantioselective Rh-Catalyzed Conjugate Additions - Fairhurst, Nathan W. G.; Munday, Rachel H.; Carbery, David R. (Synlett, 2013)
Simple oxazolidine-based chiral diene ligands, ultimately derived from serine, have been synthesized using the Seebach self-regeneration of stereocenters strategy. The ligands have been used in the enantioselective Rh-catalyzed conjugate addition of aryl boronic acids to cyclohexenone. An efficient ‘in vacuo’ reaction protocol has been developed as part of this study.
Keywords: dienes; chirality; enantioselectivity; rhodium; oxazolidines